Can Male Mice Develop Preference Towards Gentle Stroking by an Experimenter?. (1st June 2021) - Cho, C.; Chan, C.; Martin, L.J.
Highlights: Male mice display tactile conditioned place preference to gentle stroking by an experimenter. Male mice displayed significant preference towards the experimenter's hand using the three-chamber test of social approach. Weak relationship was observed between preference to gentle stroking and preference toward experimenter's hand. Abstract: Gentle stroking, a type of affective touch that holds hedonic and rewarding value, is critical to our daily inter-individual communication. This positive socio-emotional aspect of touch is conveyed through a subclass of C afferents known as C-Tactile fibers in humans with an analogous system in rodents proposed. Here, we describe a novel tactile conditioned place preference paradigm using mice and demonstrate that gentle stroking by an experimenter is rewarding. In order to investigate the relationship between tactile preference and innate sociability, mice were subjected to the classic three-chambered test of social approach, where mice displayed significant preference towards the experimenter's hand. These findings suggest that gentle stroking evoked by an experimenter can play an important role in reward and preference and establish an affiliative relationship between mice and humans. Future research can potentially use this model to examine fiber type involvement and elucidate the significance of these findings for activation of the reward system.